FAKTOR-FAKTOR YANG MEMPENGARUHI COST OF EQUITY CAPITAL PERUSAHAAN PUBLIK DI INDONESIA - Suryani, Ade Irma (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to test the influence of voluntary disclosure, information asymmetry, beta stocks, and companyâs size to the cost of equity capital. The samples are 30 companies which are selected by using purposive sampling from the manufacturer companies which are listed in Indonesia Stock Exchange during the year of 20011 until 2012. The statistic test instrument of SPSS16 is used to test both the classic assumption and multiple regression analysis. The research result shows that the research regression model is fulfilled the classic assumption test in overall, which means that the regression model is free from heteroskedaticity, multicollinearity, dan autocorrelation, and the data produced has been distributed normally. The multiple regression analysis shows that voluntary disclosure has negative influence to the cost of equity capital, information asymmetry has no influence to the cost to equity capital, beta has no influence to the cost of equity capital and companyâs size has negative influence to the cost of equity capital.Keywords: voluntary disclosure, information asymmetry, beta stocks, companyâs size, and cost of equity capital.